2022
DOI: 10.1101/2022.07.12.499637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Region Capture Micro-C reveals coalescence of enhancers and promoters into nested microcompartments

Abstract: Although enhancers are central to the regulation of mammalian gene expression, the mechanisms underlying Enhancer-Promoter (E-P) interactions remain unclear. Chromosome conformation capture (3C) methods effectively capture large-scale 3D genome structure but struggle to achieve the depth necessary to resolve fine-scale E-P interactions. Here, we develop Region Capture Micro-C (RCMC) by combining MNase-based 3C with a tiling region-capture approach and generate the deepest 3D genome maps reported thus far with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 53 publications
8
41
0
Order By: Relevance
“…In contrast, we found that PLAC-seq shows a very weak enrichment of interactions at DHSs, even for those bound by CTCF. Thus, in line with other recent reports on MNase-based C-methods 6,30,31,[39][40][41] , our results suggest that MChIP-C achieves superior sensitivity and resolution compared to C-methods based on standard restriction enzymes.…”
Section: Mchip-c Provides a Sensitive Genome-wide View Of Promoter-ce...supporting
confidence: 92%
“…In contrast, we found that PLAC-seq shows a very weak enrichment of interactions at DHSs, even for those bound by CTCF. Thus, in line with other recent reports on MNase-based C-methods 6,30,31,[39][40][41] , our results suggest that MChIP-C achieves superior sensitivity and resolution compared to C-methods based on standard restriction enzymes.…”
Section: Mchip-c Provides a Sensitive Genome-wide View Of Promoter-ce...supporting
confidence: 92%
“…5, Additional file 2: Figure S7). Previous capture Micro-C and MNase 3C capture studies [39][40][41] were focused on targeted regions and may provide higher sensitive signals using a relatively small number of reads. However, these methods detect limited chromatin interactions at the target regions while promoter capture Micro-C detects chromatin interactions of all promoter regions throughout the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, different from models that are pre-trained and fine-tuned on DNA sequence only [9, 15], EPCOT learns cell-type specific representations from DNA sequence with chromatin accessibility signals, which is generalizable to new, unseen human cell and tissue types by only requiring cell-type specific chromatin accessibility data as input. Here, chromatin accessibility is leveraged to provide cell-type specific information due to its connection with TF binding, gene regulation, and chromatin contacts [16, 17, 18]. Furthermore, EPCOT trained on human cell types can be generalized to mouse cell and tissue types.…”
Section: Mainmentioning
confidence: 99%